Topical problems of legislative regulation of defense mandatory participation in criminal proceeding - Korcheva , Tetyana (Problems of legality, 2022)
For a certain category of persons in particular cases legislator provides for a special procedure of criminal proceedings as well as mandatory participation of a defender (Article 52, The Code of Criminal Procedure) to create additional person defense guarantees in criminal proceedings. The article is devoted to study of problem aspects of legislative regulation of defense mandatory participation in criminal proceedings. The importance of defense mandatory participation is emphasized as rendering legal aid to a person in criminal proceedings. This article is devoted to study the importance of the mandatory participation of a defender in criminal proceedings and on the basis of obtained data, with due consideration of international standards of human rights protection in criminal proceedings, to submit substantiated author’s proposals as regards the expansion of the circle of grounds for the mandatory participation of a defender in Ukrainian criminal proceedings. Within the topic of study we analyzed criminal procedural legislation in force, research works in this area, decisions of European Court oh Human Rights, aiming to reveal deficiencies in law and submit author’s proposals as regards their elimination. According to normative sense of Article 52, The Code of Criminal Procedure of Ukraine, the article gives classification of the grounds for mandatory participation of a defender depending on: 1) consideration of severity of a crime; 2) consideration of personal data of a defendant held criminally liable; 3) peculiarities of criminal proceedings. Proposals are presented aimed to improve legislative regulation of Ukrainian criminal procedural law. It is proposed to add one more reason connected to the circumstance that the defendant denies suspicion against him/her and/or denies his/her guilt in commission of criminal offense. The proposal consists in addition to Article 52, Part 2, The Code of Criminal Procedure of Ukraine of new Item 10 postulating the mandatory participation of a defender in criminal proceedings against persons who deny a suspicion as specified in Suspicion Notice on deny pleading guilty at court session.